Vom Lohnarbeiter zum Shareholder? - Priewe, Jan (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2001)
The paper investigates the impact of some features of the 90s in Germany: shareholder-value orientation and changes in the distribution of share capital, booming asset prices, profit-sharing schemes including option plans, increased capital funded old-age provisions. Two propositions are discussed and, finally, denied: Due to these trends there might emerge a tendency towards a more equal distribution of capital stocks, and a relevant portion of employees might turn out as shareholders with considerable non-wage income. However, despite severe shortcomings in the data base a wave of further wealth concentration can be observed, and the workers´ share in capital assets has remained insignificant, apart from a small but increasing stratum of middle and high income employees.